The Role of Leader-Member Exchange in Elevating Local Government Employees’ Organizational Citizenship Behavior: An Empirical Evidence from East Coast Malaysia - Rashidah, Mohamad Ibrahim; Wan Abd Aziz, Wan Mohd Amin; Munir, Salleh (2014)
Arising from high level of complaints by the public on dissatisfaction on service quality provided by local government, this study was carried out to evaluate the perception of local governments’ employees on leader-member exchange (LMX) towards organizational citizenship behavior (OCB). The sample consisted of 212 respondents from six local governments in east coast Malaysia. Finding showed that OCB and LMX levels among these respondents were moderate. Two distinct factors for LMX emerged and named contribution-respect and affect-loyalty where contribution-respect showed a stronger correlation (r = 0.62, p < 0.01) compared to affect loyalty (r = 0.34, p < 0.01) towards OCB. Hierarchical regression analyses showed that 39% of variance in OCB was explained by LMX. Therefore, fostering quality dyadic relationship should not be neglected as evidence showed that quality relationship is an avenue to elicit employees’ OCB which in turn instill public confidence towards the multifarious services provided by local government.